Statins and intracerebral hemorrhage: collaborative systematic review and meta-analysis. - Hackam, D; Woodward, M; Newby, L; Bhatt, D; Shao, M; Smith, E; Donner, A; Mamdani, M; Douketis, J; Arima, H; Chalmers, J; MacMahon, S; et al. (2011)
BACKGROUND: A recent large, randomized trial suggested that statins may increase the risk of intracerebral hemorrhage. Accordingly, we systematically reviewed the association of statins with intracerebral hemorrhage in randomized and observational data. METHODS AND RESULTS: We screened 17 electronic bibliographic databases to identify eligible studies and consulted with experts in the field. We used DerSimonian-Laird random-effects models to compute summary risk ratios with 95% confidence intervals. Randomized trials, cohort studies, and case-control studies were analyzed separately. Only adjusted risk estimates were used for pooling observational data. We included published and unpublished data from 23 randomized trials and 19 observational studies. The complete data set comprised 248 391 patients and 14 784 intracerebral hemorrhages. Statins were not associated with an increased risk of intracerebral hemorrhage in randomized trials (risk ratio, 1.10; 95% confidence interval, 0.86-1.41), cohort studies (risk ratio, 0.94; 95% confidence interval, 0.81-1.10), or case-control studies (risk ratio, 0.60; 95% confidence interval, 0.41-0.88). Substantial statistical heterogeneity was evident for the case-control studies (I(2)=66%, P=0.01), but not for the cohort studies (I(2)=0%, P=0.48) or randomized trials (I(2)=30%, P=0.09). Sensitivity analyses by study design features, patient characteristics, or magnitude of cholesterol lowering did not materially alter the results. CONCLUSIONS: We found no evidence that statins were associated with intracerebral hemorrhage; if such a risk is present, its absolute magnitude is likely to be small and outweighed by the other cardiovascular benefits of these drugs.